An Empirical Re-examination: Non-oil Export, Capital Formation and Economic Growth Nexus in Nigeria. (June 2017) - Anthony-Orji, Onyinye I.; Orji, Anthony; Ogbuabor, Jonathan E.; Nwosu, Emmanuel
The current decline in global oil prices and the attendant economic distortions it has caused in many oil-dependent economies, such as Nigeria, have become a cause of concern to researchers and economic managers alike. This research work, therefore, investigates the impact of non-oil export (NOIL) on capital formation and economic growth in Nigeria. It adopts a classical linear macroeconomic model using aggregate data time series from 1980 to 2013. Empirical results from the estimated model show that NOIL has a positive impact on capital formation and economic growth in Nigeria, respectively. However, the level of statistical significance differs between capital formation and economic growth. The study, therefore, recommends that there is a need for diversification of the economy as this will go a long way in boosting the growth of the Nigerian economy. Furthermore, the government should create an enabling environment that will ensure the survival and functioning of the ailing industries in order to diversify the economy. Finally, the problem of infrastructural deficits (water supply, transport system, telecommunication and energy) should be tackled by massive public expenditure and private investment, as this will enhance productivity in the non-oil sectors.